2021
DOI: 10.3389/fonc.2020.606741
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Features Predict Telomerase Reverse Transcriptase Promoter Mutations in World Health Organization Grade II Gliomas via a Machine-Learning Approach

Abstract: The detection of mutations in telomerase reverse transcriptase promoter (pTERT) is important since preoperative diagnosis of pTERT status helps with evaluating prognosis and determining the surgical strategy. Here, we aimed to establish a radiomics-based machine-learning algorithm and evaluated its performance with regard to the prediction of mutations in pTERT in patients with World Health Organization (WHO) grade II gliomas. In total, 164 patients with WHO grade II gliomas were enrolled in this retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Several studies have analyzed the value of MRI based radiomics to predict the TERTp-mutation status in brain tumour patients [49][50][51]. Although these studies reported to achieve high accuracy values in the range of 79.88-93.80%, only WHO grade II or/and III gliomas have been considered and a limited number of patients has been investigated [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have analyzed the value of MRI based radiomics to predict the TERTp-mutation status in brain tumour patients [49][50][51]. Although these studies reported to achieve high accuracy values in the range of 79.88-93.80%, only WHO grade II or/and III gliomas have been considered and a limited number of patients has been investigated [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have analyzed the value of MRI based radiomics to predict the TERTp-mutation status in brain tumour patients [49][50][51]. Although these studies reported to achieve high accuracy values in the range of 79.88-93.80%, only WHO grade II or/and III gliomas have been considered and a limited number of patients has been investigated [49][50][51]. Besides, Tian et al established a multiparameter MRI based radiomics model for the prediction of the TERTp-mutation status in patients with high-grade glioma [52], but ignored that TERTp-mutations play different roles in different IDH phenotypes [48].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians attempt to evaluate histopathological features and glioma genomics from non-invasive imaging using AI. Radiomics based on multimodal MRI can precisely differentiate among glioma molecular, including IDH [ 109 ], MGMT [ 110 ], TERT [ 111 ] and H3 K27M [ 112 ]. A study established SVM models for detecting IDH and TP53 mutations, and the detecting accuracies for IDH and TP53 mutations on the development cohort were 84.9% and 92.0%, while that on the validation cohort were 80.0% and 85.0%, respectively [ 113 ].…”
Section: Emerging Application Of Artificial Intelligencementioning
confidence: 99%
“…Fang et al [67] extracted a total of 1293 radiomics features from preoperative MRI images (T1WI, CE-T1WI, and T2WI sequences) of 164 patients with WHO grade II gliomas and built a model for predicting TERT promoter mutation status based on the 12 most valuable radiomics features selected by nested 10-fold cross-validation cycle. The results showed that the overall accuracy was 79.88%, and the AUC was 0.8446.…”
Section: Tert Promoter Mutationmentioning
confidence: 99%